UJI EFEKTIVITAS EKSTRAK ETANOL KULIT BUAH TERONG UNGU (Solanum melongena L.) SEBAGAI ANTIHIPERGLIKEMIK TERHADAP MENCIT (Mus musculus) - Ananda Ramadani (Jurnal Kesehatan Yamasi Makassar, 2022)
This study aims to determine the effect of purple eggplant skin ethanol extract (Solanum melogena L.) on glucose-induced blood sugar levels (Mus musculus). The extract is carried out by maceration with a solvent of 95%. Mice are divided into 3 groups, consisting of 5 mice, namely the negative group (NaCMC), positive group (Glibenklamid) and purple eggplant skin extract test group (Solanum melogena L.) each group induced peroral glucose. 30 minutes later mice are treated orally and performed termination for 5 hours. The results of the study after analyzed that the suspension of purple eggplant skin ektrak gives a decreased effect of blood glucose on mice for positive control of glibenclamide provides a decreased effect of blood sugar and for the suspension of NaCMC does not provide a decreased effect of blood sugar. The calculations showed the influence of purple eggplant bark extract (Solanum melogena L.) against the decrease in blood glucose in mice.